International Brethren conference on missions ; 1 - Tunnicliffe, Geoff; Rowdon, Harold H.; Newton, Ken; International Brethren Conference on missions Singapore July 1993 (1993)
Contents : tape 1 : "Church unity and missions"/ Geoff Tunnicliffe "Brethren contribution to missions"/ Harold Rowdon "Bible and missions"/ Ken Newton
Keywords: Brethren movement -- missions -- congresses